Application of the Barcelona Clinic Liver Cancer therapeutic strategy and impact on survival. Issue 3 (June 2015) - Hernández-Guerra, Manuel; Hernández-Camba, Alejandro; Turnes, Juan; Ramos, Luis Martin; Arranz, Laura; Mera, José; Crespo, Javier; Quintero, Enrique
Background: The Barcelona Clinic Liver Cancer (BCLC) classification of hepatocellular carcinoma (HCC) has proved useful in the management of HCC patients. However, BCLC-recommended first-line treatment is not always applicable in clinical practice. Objective: We performed a multicentre retrospective analysis of reasons for deviation from first-line treatment in 2008–2012. Methods: One to three-year survival data were analysed using Kaplan-Meier method. Results: A total of 407 consecutive HCC patients (66.6 ± 3 years, 83% male) with cirrhosis were included. Tumours were detected during surveillance in 53% of patients, grouped as Child-Pugh A (67%), B (25%) and C (8%); and BCLC A (including stage 0, 44%), B (26%), C (15%) and D (15%). In 31% of patients, first-line treatment was not feasible (51% in early stages) due to: technical reasons (74%); patient non-conformity (20%); medical decision (3%); and disease progression (3%). One to three-year survival of patients not receiving the recommended first-line treatment was similar to that of patients treated according to BCLC recommendations (log-rank, p = 0.229). Conclusion: In real-life practice one-third of HCC patients could not receive first-line BCLC treatment. In our cohort of patients, similar short and medium-term survival was observed. Long-term prospective studies are required to determine the best alternative treatment option when BCLC first-line treatment is not feasible.